10-year systematic literature review of social penetration in online communication - May, Sarah Poh Low; Bolong, Jusang; Waheed, Moniza; Wirza, Julia (Human Resource Management Academic Research Society, 2022)
Altman and Taylor's (1973) Social Penetration Theory (SPT) suggests that in any relationship or communication pathway, each participant makes a conscious decision to either increase or decrease the level of self-information disclosure based on an evaluation of the advantages and disadvantages of maintaining the relationship over an unspecified period. An examination of the literature on the effect of online communication on the theory indicates that significant alterations have happened in the social penetration theory, altering the communication process and, therefore, the sorts of connections resulting from computer-mediated platforms. After extensive screening and assessment, 18 articles were selected via a review of the available literature. Subsequently, a thematic analysis of the literature revealed the following primary themes: motives and expectations, privacy, audience, interaction, audience, and adjustments. The review encountered obstacles, such as the small selection of published materials. This article focuses on SPT in digital communication, with most literature focusing on online social networks. Recommendations were made that the very dynamic and ever-changing character of social penetration in online communication should be based on conversation and interactions rather than theory.